The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0037-86822012000100019
|View full text |Cite
|
Sign up to set email alerts
|

Geographic analysis on the occurrence of human and canine leptospirosis in the city of Maringá, state of Paraná, Brazil

Abstract: INTRODUCTION: Leptospirosis is a zoonotic disease, the primary hosts of which are wild, synanthropic, and household animals. Humans behave as terminal and accidental hosts. The prevalence of leptospirosis depends on carrier animals that disseminate the agent, on the environmental survival of this agent, and on the contact of susceptible individuals. Each serovar has one or more hosts with different adaptation levels. The focuses of leptospirosis are infected, sick, and asymptomatic animals, which are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 10 publications
2
24
0
1
Order By: Relevance
“…The serogroups associated with human infection (6) (13) (14) also suggest that the role of dogs in human infection may be limited or non-existent (15) . Regardless, there is general consensus that canine disease acts as an indicator for METHODS human exposure risk (16) ; dogs are more frequently exposed to known risk factors of disease and thus may act as sentinels of environmental contamination (15) (17) . (17) , 30.5% in dogs treated in a Veterinary Teaching Hospital in Northern State (24) , and 32.2% (n = 598) in diagnostic serum samples taken from dogs in Curitiba (23) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The serogroups associated with human infection (6) (13) (14) also suggest that the role of dogs in human infection may be limited or non-existent (15) . Regardless, there is general consensus that canine disease acts as an indicator for METHODS human exposure risk (16) ; dogs are more frequently exposed to known risk factors of disease and thus may act as sentinels of environmental contamination (15) (17) . (17) , 30.5% in dogs treated in a Veterinary Teaching Hospital in Northern State (24) , and 32.2% (n = 598) in diagnostic serum samples taken from dogs in Curitiba (23) .…”
mentioning
confidence: 99%
“…Regardless, there is general consensus that canine disease acts as an indicator for METHODS human exposure risk (16) ; dogs are more frequently exposed to known risk factors of disease and thus may act as sentinels of environmental contamination (15) (17) . (17) , 30.5% in dogs treated in a Veterinary Teaching Hospital in Northern State (24) , and 32.2% (n = 598) in diagnostic serum samples taken from dogs in Curitiba (23) . Only one study of incidence rates in dogs has been conducted, which reported an annual incidence of 28.9% in a slum community of Curitiba City (25) .…”
mentioning
confidence: 99%
“…In particular, the seroprevalence values have been reported to range from 10.5% to 34.8% in the southern region of Brazil, between 6.6% and 17.9% in the southeast, between 10% and 30.9% in the midwest, at 27.3% in the north and between 20% and 85% in the northeast. The most prevalent serovars have been Canicola, Copenhageni and Pyrogenes [4][5][6][7][8] . Serology for leptospirosis lasts three months for any serovar.…”
mentioning
confidence: 99%
“…The Copenhageni and Pyrogenes serovars detected in this study can reportedly infect humans (GONÇALVES, 2009;FONZAR;LANGONI, 2012). In Brazil, there were 1,827 deaths from leptospirosis between 2011 to 2016 according to the National Medical Service System (SINAM, c2016), and so epidemiological studies to investigate patterns of infection and establish the dominant causative serovars are crucial for disease prevention and public health education measures.…”
Section: Discussionmentioning
confidence: 84%
“…This serovar is now routinely included in serological assays for infection with Leptospira for several animal species, and recent studies have shown its prevalence in goats and sheep (HIGINO; AZEVEDO, 2014), dogs (FONZAR;LANGONI, 2012;MASCOLLI et al, 2016;SAMIR et al, 2015), and humans (FONZAR; LANGONI, 2012;SAMIR et al, 2015;BRASIL, 2010b).…”
Section: Discussionmentioning
confidence: 99%